1993
DOI: 10.1097/00004032-199309000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Residual 152Eu and 60Co Activities Induced by Neutrons from the Hiroshima Atomic Bomb

Abstract: Specific activities of 152Eu:Eu in stone samples exposed to the Hiroshima atomic bomb were determined for 70 samples up to a 1,500-m slant range from the epicenter. The specific activities of 60Co:Co were also determined for six samples near the Hiroshima hypocenter. First, the 152Eu data were investigated to find out the directional dependence of neutron activation. Directional anisotropy was not definite; however, there was an indication that the activation in the west-southwest was lower than in other direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 0 publications
3
15
0
Order By: Relevance
“…This difference has been termed the "Hiroshima -~ 10.0 thermal neutron discrepancy". As indicated above, the o ~ radionuclides 152Eu and 6~ were assessed independently by Japanese teams, by means of gamma spectroscopy, and _-3 1.0 O9 the results were in apparent agreement with those obtained for 36C1, for large distances from the epicenter in Hiroshima [6,8,9,10,11,19,21,23,24,25,26,27] ( Fig. 1).…”
Section: Introductionsupporting
confidence: 73%
“…This difference has been termed the "Hiroshima -~ 10.0 thermal neutron discrepancy". As indicated above, the o ~ radionuclides 152Eu and 6~ were assessed independently by Japanese teams, by means of gamma spectroscopy, and _-3 1.0 O9 the results were in apparent agreement with those obtained for 36C1, for large distances from the epicenter in Hiroshima [6,8,9,10,11,19,21,23,24,25,26,27] ( Fig. 1).…”
Section: Introductionsupporting
confidence: 73%
“…(18)] at distances from the hypocenter where people could survive, and these results were in close agreement with calculated values in the investigated samples. In addition, new measurements of thermal-neutron-induced 36 Cl also showed a reasonable agreement with the DS02 calculations (19)(20)(21)(22)(23)(24), even at distances beyond 1,000 m from the hypocenter where previous studies found poor agreement with neutron transport calculations (25,26).…”
Section: Introductionsupporting
confidence: 72%
“…Filled circles indicate the ratios measured by Komura, et al 3) . Filled and open squares indicate the ratios measured by Shizuma, et al 4,5) . Filled triangles indicate the ratios measured by Nakanishi et al 6) .…”
Section: Samplesmentioning
confidence: 98%
“…Because of the long life (13.537 y) 1) , the 152 Eu activities are still measurable. Many investigations have been performed for measuring the 152 Eu/Eu ratios in the rock samples exposed to the Hiroshima atomic bomb [2][3][4][5][6][7][8] . The data on the .…”
Section: Introductionmentioning
confidence: 99%